2001
DOI: 10.1007/pl00000827
|View full text |Cite
|
Sign up to set email alerts
|

Contributions in the domain of cancer research: Review¶Human papillomaviruses and their role in cervical cancer

Abstract: Human papillomaviruses (HPVs) have been linked to a variety of human diseases, most notably cancer of the cervix, a disease responsible for at least 200,000 deaths per year worldwide. Over 100 different types of HPV have been identified and these can be divided into two groups. Low-risk HPV types are the causative agent of benign warts. High-risk HPV types are associated with cancer. This review focuses on the role of high-risk HPV types in cervical tumorigenesis. Recent work has uncovered new cellular partner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
45
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(45 citation statements)
references
References 223 publications
(213 reference statements)
0
45
0
Order By: Relevance
“…Several histopathologic results confirmed that inflammation is much more common in the transition zone and peripheral zone of the prostate gland, which is a prediction for BPH and PCa (Hamid et al, 2011). A relationship between HPV infection and prostate carcinoma has been suggested and some studies demonstrated and confirmed that HPV infection play a main role in the progression and tumorigenesis (Dell and Gaston, 2001;Maghrabi et al, 2007).…”
mentioning
confidence: 98%
“…Several histopathologic results confirmed that inflammation is much more common in the transition zone and peripheral zone of the prostate gland, which is a prediction for BPH and PCa (Hamid et al, 2011). A relationship between HPV infection and prostate carcinoma has been suggested and some studies demonstrated and confirmed that HPV infection play a main role in the progression and tumorigenesis (Dell and Gaston, 2001;Maghrabi et al, 2007).…”
mentioning
confidence: 98%
“…[1][2][3][4] During productive infection, the virus gains access to the basal epithelium where the viral DNA replicates to a low level of approximately 50 copies per infected cell. [1][2][3][4] Virion production requires terminal differentiation of the host cell during which the virus replicates to high levels, produces the capsid proteins L1 and L2, and mature virions are formed. [1][2][3][4] The shed virions then reinfect the basal epithelium or they can infect new hosts.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Virion production requires terminal differentiation of the host cell during which the virus replicates to high levels, produces the capsid proteins L1 and L2, and mature virions are formed. [1][2][3][4] The shed virions then reinfect the basal epithelium or they can infect new hosts. PVs infect many different species of animals in nature, and to date more than 100 types of human papillomaviruses (HPVs) have been identified.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations